NEED AND EXPECTATIONS FOR LEARNING IN A STEM ENVIRONMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In the last decade, the need for specialists in the field of engineering and exact sciences emerged in Bulgaria and around the world. This led to the launch of a National Program for the construction of stem centers in schools. From the Veliko Tarnovo region, 16 schools joined the program at different stages, where STEM centers are being built or are already functioning in various subjects, which significantly support the preparation of quality personnel for the Bulgarian economy. A review and analysis of the expectations of teachers and students from work in centers with an engineering focus and training in natural sciences was made. At the next stage, an analysis and evaluation of the effect of the implementation of these innovative centers will be done.